ANALISIS PENENTU HARGA OBAT E-CATALOGUE PADA PT. KIMIA FARMA, TBK PERIODE 2018-2022 - Eka Rachmadi; Syahfirin Abdullah; Tatan Sukwika (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
This study aims to analyze the efficiency factors of drug production that influence e-catalogue drug prices at PT. Kimia Farma, Tbk for the 2018-2022 period. This research uses a descriptive quantitative descriptive approach by collecting secondary data in the form of generic product price data from PT. Kimia Farma, Tbk won the e-catalogue during that period as well as primary data obtained by conducting interviews. The data analysis technique used is multiple linear regression. The research results show that partially, the factors of active drug raw materials, excipient materials, production processes, and the rupiah exchange rate have a significant effect on the average price of e-catalogue drugs per semester. Meanwhile, the factors of packaging materials and production capacity do not have a significant effect. Simultaneously, these six factors have a significant influence on the average price of e-catalogue medicines per semester. The most dominant factor influencing e-catalogue drug prices is the active drug raw materials. The implication of this research is that PT. Kimia Farma, Tbk needs to pay attention to efficiency factors such as active drug raw materials, excipient materials, production processes, and the rupiah exchange rate to be able to set competitive e-catalogue drug prices in the National Health Insurance era.